2022
DOI: 10.3390/jcm11030777
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 (ACE2), Transmembrane Peptidase Serine 2 (TMPRSS2), and Furin Expression Increases in the Lungs of Patients with Idiopathic Pulmonary Fibrosis (IPF) and Lymphangioleiomyomatosis (LAM): Implications for SARS-CoV-2 (COVID-19) Infections

Abstract: We previously reported higher ACE2 levels in smokers and patients with COPD. The current study investigates if patients with interstitial lung diseases (ILDs) such as IPF and LAM have elevated ACE2, TMPRSS2, and Furin levels, increasing their risk for SARS-CoV-2 infection and development of COVID-19. Surgically resected lung tissue from IPF, LAM patients, and healthy controls (HC) was immunostained for ACE2, TMPRSS2, and Furin. Percentage ACE2, TMPRSS2, and Furin expression was measured in small airway epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Furthermore, our research group previously reported that ACE2, Furin and Transmembrane protease serine 2 (TMPRSS2) receptors are upregulated in IPF facilitating SARS-CoV-2 infection [19]. We have reported similar findings in smokers and patients with COPD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, our research group previously reported that ACE2, Furin and Transmembrane protease serine 2 (TMPRSS2) receptors are upregulated in IPF facilitating SARS-CoV-2 infection [19]. We have reported similar findings in smokers and patients with COPD.…”
Section: Discussionsupporting
confidence: 63%
“…A synergy between bacteria and virus has been documented, detailing that it causes superinfections that exacerbate IPF progression, reducing lung function and lowering the survival rate compared to uninfected patients [15]. Similarly, SARS-CoV-2 receptor angiotensinconverting enzyme 2 (ACE2) has been shown to upregulate in patients with IPF, increasing their susceptibility to COVID-19 [15,19]. With this knowledge, we wanted to investigate the presence of other potential microbial receptors, such as platelet-activating factor receptor (PAFR) and intracellular adhesion molecule-1 (ICAM-1), and their possible involvement in microbial entry into host cells [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…They found TGF-β1 and α-smooth muscle actin (myofibroblast marker) are in similar areas as COVID-19 markers. They suggest that myofibroblasts and surrounding tissue secrete growth factors which could further affect COVID-19 adhesion proteins/cofactors and post-COVID-19 interstitial pulmonary fibrosis ( 37 ). Our study confirms that entry factors are negatively correlated with early EndMT cell fraction and are positively correlated with fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Some hypotheses, including ours, implicate sex steroids in differential effects of COVID-19. For example, we observed higher baseline expression of the ACE2 receptor in the ASM in males compared to females [ 208 , 215 ]. More importantly, when age-matched male and female ASM cells were exposed to physiological concentrations of the sex steroids independently, testosterone increased ACE2 expression, whereas estrogen downregulated ACE2 in ASM [ 208 ].…”
Section: Coronavirus Disease: What’s Sex/sex Steroids Got To Do With It?mentioning
confidence: 99%